1986
DOI: 10.1104/pp.82.4.930
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin-Induced Ethylene Biosynthesis in Nonsenescing Cotton Leaves

Abstract: The influence of cytokinins on ethylene production was examined using cotton leaf tissues. Treatment of intact cotton (Gossypium hirsutum L. cv LG 102) seedlings with both natural and synthetic cytokinins resulted in an increase in ethylene production by excised leaves. The effectiveness of the cytokinins tested was as follows: thidiazuron >> BA >> isopentyladenine 2 zeatin >> kinetin. Using 100 micromolar thidiazuron (TDZ), an initial increase in ethylene production was observed 7 to 8 hours posttreatment, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
5
30
0
1
Order By: Relevance
“…However, ACC was increased by the compounds with nearly the same order of activity as ethylene (Table I). This supports previous results of a cytokinin-induced, ACC-dependent ethylene formation (17). With the exception of Kn, which was comparatively more effective in increasing ethylene than in defoliating, a close correlation between both cytokinin-stimulated activities was observed (r = 0.88, P < 0.01; calculated from data presented in Fig.…”
Section: Ethylene Formation and Acc And Macc Levels In Leaf Discssupporting
confidence: 79%
See 1 more Smart Citation
“…However, ACC was increased by the compounds with nearly the same order of activity as ethylene (Table I). This supports previous results of a cytokinin-induced, ACC-dependent ethylene formation (17). With the exception of Kn, which was comparatively more effective in increasing ethylene than in defoliating, a close correlation between both cytokinin-stimulated activities was observed (r = 0.88, P < 0.01; calculated from data presented in Fig.…”
Section: Ethylene Formation and Acc And Macc Levels In Leaf Discssupporting
confidence: 79%
“…In cotton, ethylene production was increased by thidiazuron as well as by natural and synthetic cytokinins of adenine type (17). However, little information has been given in the literature on the potency of adenine-type cytokinins in defoliating cotton.…”
mentioning
confidence: 99%
“…Previous studies have shown that treatment of intact cotton seedlings with TDZ results in an increase in ethylene production within 8 h while leaf abscission commences within 72 h (16,17). These responses were most apparent in the younger, recently expanded leaves.…”
Section: Resultsmentioning
confidence: 84%
“…Cotton (Gossypium hirsutum L. cv LG 102) seedlings were grown in a growth chamber as described previously (17). In Auxin Transport Assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation